The Prognostic Role of Blood Inflammatory Biomarkers and EGFR Mutation Status in Stage IIIA/N2 Non-Small Cell Lung Cancer Patients Treated With Trimodality Therapy - Yang, Hui; Wang, Kunlun; Li, Bingxu; Li, Shenglei; Li, Yan; Yuan, Ling (Frontiers in Oncology, 2021)
Objectives: Various blood inflammatory biomarkers were associated with treatment response and prognosis of non-small cell lung cancer (NSCLC) in previous studies. In this study, we retrospectively evaluated the prognostic role of pretreatment blood inflammatory biomarkers and epidermal growth factor receptor (EGFR) mutation status in stage IIIA/N2 NSCLC patients with trimodality therapy. Methods: Completely resected stage IIIA/N2 NSCLC patients with adjuvant chemotherapy and postoperative radiotherapy (PORT) were assessed in this study. Cutoff values of blood inflammatory factors were calculated by the R package SurvivalROC of R software. SPSS Statistics software were used for survival analyses. Kaplan-Meier survival curve and log-rank test were used to compare the survival difference between every two groups. Univariate and multivariate analyses of predictive factors were performed by Cox proportional hazards regression model. Results: The univariate analysis showed that T stage (p=0.007), EGFR mutation status (p=0.043), lymphocyte-to-monocyte ratio (LMR) (p=0.067), and systemic immune-inflammation index (SII) (p=0.043) were significant prognostic factors of disease-free survival (DFS). In the multivariate analysis, T2 (HR=0. 885, 95% CI: 0.059-0.583, p=0.004), EGFR mutation-positive (HR=0.108, 95% CI: 0.023-0.498, p=0.004) and elevated pretreatment SII (HR=0.181, 95%CI: 0.046-0.709, p=0.014) were independently related to shorter DFS. High pretreatment neutrophil counts (HR=0.113, p=0.019) and high systemic inflammation response index (SIRI) (HR=0.123, p=0.025) were correlated with worse overall survival (OS) by the univariate analysis. In the multivariate analysis, only high pretreatment SIRI was an independent predictor for poorer OS (HR=0.025, 95% CI: 0.001-0.467, p=0.014). Conclusions: In conclusion, we identified that high pretreatment SII and SIRI were unfavorable prognostic factors in stage IIIA/N2 NSCLC patients treated with surgery, adjuvant chemotherapy and PORT. Patients with high pretreatment SII, high pretreatment SIRI, T2, and EGFR mutation-positive may need more forceful adjuvant treatment. Further prospective studies with large-scale are needed to validate our results and identify the proper cut-off values and optimum adjuvant treatment for distinct patient population.